Diffuse Pulmonary Adenocarcinoma with Micropapillary Growth Pattern in a Cat. (April 2018) - Romanucci, M.; Massimini, M.; Aste, G.; Defourny, S.V.P.; Crisi, P.E.; Boari, A.; Della Salda, L.
Summary: A 12-year-old female European shorthair cat was presented with severe dyspnoea. Echocardiography revealed hypertrophic cardiomyopathy and pleural effusion. The cat died from acute decompensated left heart failure. At necropsy examination, the lungs were diffusely congested and firm, with multifocal grey areas and sparse haemorrhages. No solid masses were detected. Histopathology revealed a diffuse neoplastic proliferation characterized by irregular growth along alveolar walls with a micropapillary pattern. Tumour cells were large, highly pleomorphic and intensely positive for pan-cytokeratin and CAM 5.2. Tumour growth was obscured by simultaneous lesions related to chronic pulmonary congestion and interstitial lung disease. Histological features were consistent with a diffuse invasive pulmonary adenocarcinoma with a micropapillary pattern of tumour growth. Differential diagnosis included large cell carcinoma, which is usually characterized by rosettes or solid clusters of cells occupying alveolar lumen. Extensive cytokeratin immunolabelling was helpful in the differentiation from histiocytic proliferative disease.